Trace moisture measurement in natural gas mixtures with a single calibration for nitrogen background gas. (24th July 2020) - Takeda, N; Carroll, P; Tsukahara, Y; Beardmore, S; Bell, S; Yamanaka, K; Akao, S
Abstract: The measurement and control of trace moisture is an important procedure to maintain and secure the quality and safety of pipeline systems for natural gas. The natural gas mix typically comprises methane, ethane, propane, some higher hydrocarbons, carbon dioxide and nitrogen. It is too impractical to perform additional calibrations of trace moisture measurement every time the combination of gas components in the natural gas mix is changed. This paper proposes a method to separate and compensate for the effect of the background gas composition from the trace moisture measurement by using two different frequencies in a trace moisture analyzer utilizing a ball surface acoustic wave (SAW) sensor. The experiment was performed by connecting the ball SAW trace moisture sensor to supplies of trace moisture in multiple background gases from the National Physical Laboratory (NPL) Multi-gas, Multi-pressure Standard Humidity Generator, and changing the composition of the background gases including N2, air, CH4, 80% CH4 /20% C2 H6, and 50% CH4 /50% C2 H6 . At the nominal humidity frost-point values of −70 °C, −50 °C, −40 °C and −30 °C, the deviations due to the change of the background gases were within ± 1 °C in frost point.